Reliance on condoms for contraceptive protection among HIV care and treatment clients: a mixed methods study on contraceptive choice and motivation within a generalised epidemic. (2nd April 2014) - Church, Kathryn; Wringe, Alison; Fakudze, Phelele; Kikuvi, Joshua; Nhlabatsi, Zelda; Masuku, Rachel; Initiative, Integra; Mayhew, Susannah H
Abstract : Objectives: To (i) describe the contraceptive practices of HIV care and treatment (HCTx) clients in Manzini, Swaziland, including their unmet needs for family planning (FP), and compare these with population-level estimates; and (ii) qualitatively explore the causal factors influencing contraceptive choice and use. Methods: Mixed quantitative and qualitative methods were used. A cross-sectional survey conducted among HCTx clients (N=611) investigated FP and condom use patterns. Using descriptive statistics, findings were compared with population-level estimates derived from Swaziland Demographic and Health Survey data, weighted for clustering. In-depth interviews were conducted with HCTx providers (n=16) and clients (n=22) and analysed thematically. Results: 64% of HCTx clients reported current contraceptive use; most relied on condoms alone, few practiced dual method use. Rates of condom use for FP among female HCTx clients (77%, 95% CI 71% to 82%) were higher than population-level estimates in the study region (50% HIV-positive, 95% CI 43% to 57%; 37% HIV-negative, 95% CI 31% to 43%); rates of unmet FP needs were similar when condom use consistency was accounted for (32% HCTx, 95% CI 26% to 37%; vs 35% HIV-positive, 95% CI 28% to 43%; 29% HIV-negative, 95% CI 24% to 35%). Qualitative analysis identified motivational factors influencing FP choice: fears of reinfection; a programmatic focus on condoms for people living with HIV; changing sexual behaviours before and after antiretroviral therapy (ART) initiation; failure to disclose to partners; and contraceptive side effect fears. Conclusions: Fears of reinfection prevailed over consideration of pregnancy risk. Given current evidence on reinfection, HCTx services must move beyond a narrow focus on condom promotion, particularly for those in seroconcordant relationships, and consider diverse strategies to meet reproductive needs.